Multi-Destination Beaming: Apparently Being in Three Places at Once through Robotic and Virtual Embodiment - Kishore, Sameer; Muncunill, Xavi Navarro; Bourdin, Pierre; Or-Berkers, Keren; Friedman, Doron; Slater, Mel (Frontiers in Robotics and AI, 2016)
It has been shown that an illusion of ownership over an artificial limb or even an entire body can be induced in people through multisensory stimulation providing evidence that the surrogate body is the person’s actual body. Such body ownership illusions have been shown to occur with virtual bodies, mannequins, as well as humanoid robots. In this study, we show the possibility of eliciting a full body ownership illusion over not one, but multiple artificial bodies concurrently. We demonstrate this by describing a system that allowed a participant to inhabit and fully control two different humanoid robots located in two distinct places and a virtual body in immersive virtual reality, using real-time full-body tracking and two-way audio communication, thereby giving them the illusion of ownership over each of them. We implemented this by allowing the participant be embodied in any one surrogate body at a given moment, and letting them instantaneously switch between them. While the participant was embodied in one of the bodies, a proxy system would track the locations currently unoccupied, and would control their remote representation in order to continue performing the tasks in those locations in a logical fashion. To test the efficacy of this system, an exploratory study was carried out with a fully functioning setup with three destinations and a simplified version of the proxy for use in a social interaction. The results indicate that the system was physically and psychologically comfortable, and was rated highly by participants in terms of usability. Additionally, feelings of body ownership illusion and agency were reported, which were not influenced by the robot type. The results provide us with clues regarding body ownership illusion with humanoid robots of different dimensions, along with insight about self-localization and multilocation.